1964
DOI: 10.2134/agronj1964.00021962005600050008x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen and Potassium on the Yield and Chemical Composition of Orchardgrass1

Abstract: Synopsis Nitrogen increased orchardgrass yields significantly throughout the season. However, potassium produced a significant yield increase only at the third harvest. Both nutrients depressed the percent total fructose of the sheaths during the first two growth periods. This effect was reversed for nitrogen during the third growth period. Asparagine accumulated abnormally in the second and third harvests when potassium fell below 1.6% of the dry weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
4
8
0
1
Order By: Relevance
“…Di early summer, the longest-deferred plots produced greatest yields, while during late summer, all clipping systems yielded approximately the same. As previously reported by Griffith et al, (1964), they found that high N fertilization lowered the total fructose level of the orchardgrass stubble during the early part of the growing season. more total production from 3 than 5 cuttings across all levels of applied N. They also found that less frequent harvesting improved the efficiency of N in terms of dry matter production but had little effect on crude protein.…”
Section: Other Factorssupporting
confidence: 81%
See 2 more Smart Citations
“…Di early summer, the longest-deferred plots produced greatest yields, while during late summer, all clipping systems yielded approximately the same. As previously reported by Griffith et al, (1964), they found that high N fertilization lowered the total fructose level of the orchardgrass stubble during the early part of the growing season. more total production from 3 than 5 cuttings across all levels of applied N. They also found that less frequent harvesting improved the efficiency of N in terms of dry matter production but had little effect on crude protein.…”
Section: Other Factorssupporting
confidence: 81%
“…They found a yield increase due to K when the percent K in the forage was 1.6# or less which corresponds very closely to the K percent found in orchardgrass at which an abnormal asparagine content was observed as reported by Griffith et (1964). Laughlin and Restad (1964) also found that in general K2S0^ was not superior to KCl as a K source for bromegrass.…”
Section: Five Orchardgrass Varieties From Diverse Areas Of the Unitedsupporting
confidence: 67%
See 1 more Smart Citation
“…The same situation is recognized also in some other species, for example, in orchardgrass (Griffith, Teel, and Parker, 1964;Colby et aI., 1965;Auda et aI., 1966) and coastal bermudagrass (Adegbola and McKell, 1966).…”
Section: A Accumulation Of Organic Substances and Nitrogenmentioning
confidence: 59%
“…Conversely, increased amounts of potassium have resulted in higher levels of carbohydrates in alfalfa seedlings (Matches, et al, 1963;and Re id, Lathwell, and Wright, 1965). There appears to be a balance required between potassium and nitrogen for accumulation of carbohydrates and ' normal nitrogen metabolism and protein synthesis (Griffith, Teel, and Parker, 1964;and MacLeod, 1965). Wardlaw (I968) stated carbohydrate accumu lation by nitrogen-deficient plants indicates that the growth processes of cell division and cell expansion are more affected than photosynthesis or translocation of photosynthate out of leaves.…”
Section: Effect Of Env î Ronmentmentioning
confidence: 99%